The effects of anaerobic threshold on VE/VCO2 and VE/VO2 during incremental exercise and constant load exercise test. - Algul, Sermin; Ugur, F. Ahmet; Ayar, Ahmet; Ozcelik, Oguz (Wiley-Blackwell, 2015)
[Abstract Not Available]